If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6w-11=17+8w
We move all terms to the left:
6w-11-(17+8w)=0
We add all the numbers together, and all the variables
6w-(8w+17)-11=0
We get rid of parentheses
6w-8w-17-11=0
We add all the numbers together, and all the variables
-2w-28=0
We move all terms containing w to the left, all other terms to the right
-2w=28
w=28/-2
w=-14
| m-31/6-7m-14/7=1 | | x+5=-x−11 | | -4g+19=2-5g+15 | | (3x+35)=(4x+20) | | 19x=142.5 | | 4x=9+5x | | 3c-7=4c-11 | | -18.8r-18.07-5.6r=19.55-18.7r | | x-8.2=1.8 | | x-16=20.5 | | 2.5=1.08^n | | w+6.7=-1.2 | | 1.5s=9 | | x+25=40.5 | | 15t+7=17t+17 | | -6v=-2v+16 | | 3y-14=44-y | | Y=600(1.08t) | | g-16=-8 | | Y=-5x4+3 | | 1-16j+17=-12j+10 | | Y=600(11.08t)= | | 10a+2a=36 | | 3(y-1)=40 | | x2−8x+11.1=0 | | -10y+2+9=-3-8y | | -9+9b=8b | | 2(t+5)=28 | | 3.2=x-0.48 | | -3-5v=-3v+7 | | x(.07)=4370 | | x-3+2x+2x=8 |